Maximal intermittent contractions of the first dorsal interosseous inhibits voluntary activation of the contralateral homologous muscle - Kavanagh, Justin J.; Feldman, Matthew R.; Simmonds, Michael J. (Journal of neurophysiology, 2016)
The aim of this study was to investigate how maximal intermittent contractions for a hand muscle influence cortical and reflex activity, as well as the ability to voluntarily activate the homologous muscle in the opposite limb. Twelve healthy subjects (age 24 ± 3 yr, all right-hand dominant) performed maximal contractions of the dominant limb first dorsal interosseous (FDI), and activity of the contralateral FDI was examined in a series of experiments. Index finger abduction force, FDI electromyography (EMG), motor evoked potentials, and heteronomous reflexes were obtained from the contralateral limb during brief, nonfatiguing contractions. The same measures, as well as the ability to voluntarily activate the contralateral FDI, were then assessed in an extended intermittent contraction protocol that elicited fatigue. Brief contractions under nonfatigued conditions increased index finger abduction force, FDI EMG, and motor evoked potential amplitude of the contralateral limb. However, when intermittent maximal contractions were continued until fatigue, there was an inability to produce maximal force with the contralateral limb (∼30%), which was coupled to a decrease in the level of voluntary activation (∼20%). These declines were present without changes in reflex activity and regardless of whether cortical or motor point stimulation was used to assess voluntary activation. It is concluded that performing maximal intermittent contractions with a single limb causes an inability of the central nervous system to maximally drive the homologous muscle of the contralateral limb. This is, in part, mediated by mechanisms that involve the motor cortex ipsilateral to the contracting limb.